STUDENTS INTEREST ON ENTREPREUNEUR MOVEMENTS (analytic descriptive study on students of STKIP Siliwangi Bandung) - Melpa Butarbutar; Kamaludin Kamaludin (IKIP Siliwangi Bandung, 2018)
The purpose of this research are to: 1) Describe and analyze student's response to entrepreneurship learning conducted by STKIP Siliwangi Bandung, 2) Describe and analyze student interest of STKIP Siliwangi Bandung about entrepreneurship movement, 3) Describe and analyze the effectiveness of entrepreneurship learning conducted by STKIP Siliwangi Bandung and how much that can be perceived benefits by it students, and 4) Analyze the relationship between entrepreneurship learning with student interest of being an entrepreuneur in STKIP Siliwangi Bandung. Method used in this research is analytic descriptive study with data collection techniques using entrepreuneurial questionnaire. The population in this study was the STKIP students from the PendidikanLuarSekolah Education program who have received the Entrepreneurship course study. Samples were taken as many as 20 people by proportional random sampling. The results of the research are: 1) The learning process of entrepreneurship carried out by STKIP Siliwangi Bandung get good response from the students. 2) Most students show affection in entrepreneurship although they cannot be regarded as interest of becoming an entrepreneur because it can be influenced by other external and internal factors. 3) Effectiveness of entrepreneurial learning can be perceived by students because there has been a change of students mindset that after school graduation they should not always be a job seeker but also had a chance to become an entrepreneur. 4) There is a very low relation between entrepreneurship learning and entrepreneurship interest.